Hey there.
When subtracting monomials, it's imperative that you subtract the proper terms. You cannot subtract or add a number from a variable, and you cannot do the same the other way around (unless you are multiplying).
Here's an example;
(2x + 1) + (3x + 3);
Add our variables.
2x + 3x = 5x
Add our numbers.
1 + 3 = 4.
Our final expression is 5x + 4.
Let's apply this knowledge to our current function.
f = 3x - 2
g = 2x + 1
f - g;
(3x - 2) - (2x + 1)
Remember to flip all signs of the variables and numbers to the right of the subtraction sign.
(3x - 2) - 2x - 1;
3x - 2x = x
-2 -1 = -3
We are left with x - 3.
Your answer is C.)
I hope this helps!